2015
DOI: 10.1021/acs.langmuir.5b02491
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Rheological Properties of a Pseudogemini Surfactant Formed in a Salt-Free Catanionic Surfactant Mixture in Water

Abstract: The surface and bulk properties of bola-type dicarboxylic acid (sebacic acid, SA) and zwitterionic surfactant tetradecyldimethylamine oxide (C14DMAO) mixtures in aqueous solutions were studied. Surface tension measurements indicate a pronounced synergistic effect between SA and C14DMAO. In bulk aqueous solutions, rich phase behavior was observed with a varied SA-to-C14DMAO ratio (ρ) and a total surfactant concentration. Typically at ρ = 0.5, a novel pseudogemini surfactant (C14-S-C14) forms, driven by electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Freeze-fracture transmission electron microscopy (FF-TEM) was employed to characterize the morphology of UB-NLC [ 40 , 41 , 42 , 43 , 44 ]. For freeze-fracture (FF) measurements, droplets of the sample were dropped onto a specimen holder and frozen via a rapid plunge into liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Freeze-fracture transmission electron microscopy (FF-TEM) was employed to characterize the morphology of UB-NLC [ 40 , 41 , 42 , 43 , 44 ]. For freeze-fracture (FF) measurements, droplets of the sample were dropped onto a specimen holder and frozen via a rapid plunge into liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…However, the relatively complex and diverse molecular configurations made gemini surfactants difficult to synthesize, which limits their development and application. One promising strategy is to select “pseudogemini surfactants” that are constructed through noncovalent interactions (such as electrostatic interactions and π–π stacking) between “gemini-type” organic salts and monomeric surfactants. Apparently, the pseudogemini surfactants fabricated by noncovalent interactions provide more selectivity and can effectively avoid complicated synthetic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods require complex chemical modifications and purification steps, which are quite costly. Unsaturated fatty acids can also be used simultaneously with metal hydroxides (Delample et al, 2011), calcium oxide, or organic bases (Horbaschek et al, 2000;Li et al, 2015;Zhou et al, 2014) to improve their solubility via neutralization. With protonated base as counterions, various types of self-assemblies can be obtained, including spherical micelles, wormlike micelles (Zhang et al, 2013), and bilayers/vesicles (Rasi et al, 2003) in diluted systems, liquid crystals or lamellae (Ouimet et al, 2003) in Supporting information Additional supporting information may be found online in the Supporting Information section at the end of the article.…”
Section: Introductionmentioning
confidence: 99%